Collagen and α-Tubulin of Mouse Tympanic Membrane Fibroblasts Treated with Quinolones and Aminoglycosides. (February 2017) - Milne-Davies, Bailey A.; Antonelli, Patrick J.; Orobello, Nicklas C.; Dirain, Carolyn O.
Objective: To assess collagen and α-tubulin levels of mouse tympanic membrane fibroblasts treated with quinolone and aminoglycoside antibiotics at concentrations found in eardrops. Study Design: Prospective controlled cell culture study. Setting: Academic tertiary medical center. Subjects: Mouse tympanic membrane fibroblasts. Methods: In experiment 1, fibroblasts were treated with the following for 24 or 48 hours: phosphate-buffered saline (negative control), dilute hydrochloric acid (positive control), 0.5% gatifloxacin, or commercially available 0.3% ciprofloxacin, 0.3% ciprofloxacin + 0.1% dexamethasone, 0.3% ofloxacin, 0.5% moxifloxacin, 0.3% gentamicin, or 3.5 mg/mL of neomycin + polymyxin B sulfate + hydrocortisone. In experiment 2, cells were treated with the pure form of gatifloxacin, gentamicin, ofloxacin, or ciprofloxacin. Cells were observed with phase-contrast microscope until harvested. Proteins were extracted for Western blotting with antibodies against collagen α1 type I (collagen 1A1) and α-tubulin, and for densitometry to quantify levels. Results: Collagen and tubulin levels in fibroblasts treated with ofloxacin, moxifloxacin, gatifloxacin, or gentamicin for 24 hours were not different from the saline control. Fibroblasts treated with neomycin + polymyxin B + hydrocortisone, ciprofloxacin + dexamethasone, or ciprofloxacin for 24 hours had lower collagen 1A1 and α-tubulin levels (all P < .001) than the negative control. After 48 hours, fibroblasts treated with neomycin + polymyxin B sulfate + hydrocortisone, ciprofloxacin + dexamethasone, ciprofloxacin, or moxifloxacin had lower collagen 1A1 ( P ≤ .007) and α-tubulin ( P < .0001; except ciprofloxacin, P = .033) as compared with control. In experiment 2, only cells treated with ciprofloxacin had lower collagen 1A1 and α-tubulin levels and cell viability (all P < .0001) than control. Cytotoxicity assay and phase-contrast images mirrored the protein findings. Conclusion: The adverse impact of topical antibiotic exposure on tympanic membrane collagen and tubulin protein levels is drug specific. This may be important for selection of ototopical therapy.